The Development of Teaching Materials Based on Self-Directed Learning to Improve Students’ Problem-Solving Ability - Sofiyana, Ardani Dwi Pinkan; Purnomo, Arif; Husain, Fadly (Universitas Negeri Semarang, 2025)
As the demands of educational world, which emphasizes the importance of problem-solving skills, social studies learning needs to be optimized to equip students with relevant skills for overcoming challenges in society. This study aims to design and develop teaching materials that apply self-directed learning, and also to evaluate the effectiveness of the implementation of these teaching materials in the context of social studies learning. The form of teaching materials in this study consist of a Student Book and a Teacher Book designed using an approach that emphasizes the development of students’ independence in the learning process. By producing a product that aligns with students’ needs, Research and Development (R&D) employs in this study. In the process of developing teaching materials, media expert and subject matter expert are involved to ensure the quality and success of the products. The effectiveness of the learning materials was tested through an experiment two seventh-grade classes at SMP Negeri 3 Ungaran. This study demonstrates that teaching materials applying self-directed learning can enhance students’ problem-solving skills. This finding is supported by statistical tests confirming the effectiveness of these teaching materials in achieving learning objectives.